Odpowiedzi

Najlepsza Odpowiedź!
2009-11-26T19:11:44+01:00
A.
x+2y=-2
2x-y=1

x=-2-2y
2(-2-2y)-y=1

x=-2-2y
-4-4y-y=1

x=-2-2y
-5y=5 |:(-5)

x=-2-2y
y=-1

x=-2-2(-1)
y=-1

x=0
y=-1

b.
x+4y=-2
3x-8y=10

x=-2-4y
3(-2-4y)-8y=10

x=2-4y
-6-8y-8y=10

x=2-4y
-16y=16 |: (-16)

x=2-4y
y=-1

x=6
y=-1

c.
3x-2y=5 |:(-2)
2x-y=4

y=-2,5+1,5x
2x-(-2,5+1,5x)=4

y=2,5+1,5x
2x+2,5-1,5x=4

y=2,5+1,5x
0,5x=1,5 |*2

y=2,5+1,5x
x=3

y=2,5+1.5*3
x=3

y=7
x=3

d.
2x+9y=-9 |:2
-3x+3y=8

x=-4,5-4,5y
-3(-4,5-4,5y)+3y=8

x=-4,5-4,5y
13,5+13,5y+3y=8

x=-4,5-4,5y
18,5y=-5,5 |:18,5

x=-4,5-4,5y
y=0,30

x=-4,5-4,5*0,30
y=0,30

x=5,85
y=0,30

jakos dziwnie wyszło ..co do tego nie jestem pewna

e.
2x+3y=4 |:2
8x-5y=-1

x=2-1,5y
8(2-1,5y)-5y=-1

x=2-1,5y
16-12y-5y=-1

x=2-1,5y
-17y=-17 |:(-17)

x=2-1,5y
y=1

x=0,5
y=1




  • Użytkownik Zadane
2009-11-26T19:47:52+01:00
A)(x+2y)=-2
(2x-y)=1

x=-2-2y
2*(-2-2y)-y=1

x=-2-2y
-4-4y=1

x=-2-2y
-4y=5/:(-4)

x=-2-2y
y=-1¼

x=-2-2*(-5/4)=-2+2,5=0,5

b) x+4y=-2
3x-8y=10

x=-2-4y
3*(-2-4y)-8y=10

x=-2-4y
-6+12y=10

x=-2-4y
12y=16/:12

x=-2-4y
y=1⅓

x=-2-4*4/3=-2-5⅓=-7⅓
y=1⅓

c) 3x-2y=5
2x-y=4

3x=5+2y/:3
x=1⅔+⅔y

2*(1⅔+⅔y)-y=4
3⅓+1⅓y-y=4
⅓y=⅔/:⅓
y=2

2x=4-2
2x=2
x=1

d) 2x+9y=-9
-3x+3y=8

9y=-9-2x/:9
y=-1-2/9x

-3x+3*(-1-2/9x)=8
-3x-3-⅓x=8

-3⅓x=11
x=-3,3
y=-1-2/9*(-3,3)=-4/15

e) 2x+3y=4
8x-5y=-1

2x=4-3y/:2
x=2-1,5y

8*(2-1,5y)-5y=-1
16-12y-5y=-1
-17y=-17
y=1
x=2-1,5*1=2-1,5=0,5

Koniec =)